Factors explaining participation in WhatsApp groups: an exploratory study. Issue 4 (16th July 2018) - Gazit, Tali; Aharony, Noa
Abstract : Purpose: To date, only a limited number of studies have considered WhatsApp groups. The purpose of this paper is to focus on single WhatsApp groups and explore their special characteristics and dynamics. The present study used the social support perspective, Big Five model and narcissism paradigm to predict the level of participation in WhatsApp groups with these variables. Design/methodology/approach: The research was conducted in Israel during the Spring semester of the 2017 academic year and encompassed 127 students. Researchers used eight questionnaires to gather data: a demographic questionnaire; a perceived social support questionnaire; three characteristics from the BIG5 questionnaire: extroversion, openness to experience and neuroticism; a narcissistic questionnaire; questions about WhatsApp usage; questions about one meaningful WhatsApp group; participation level in the meaningful group; and group importance. Findings: The findings confirmed that psychological factors such as social support, extroversion and narcissism significantly predict the level of participation in WhatsApp groups. It was also found that age, the level of group importance, being the group's manager, WhatsApp usage and group's subject play an important role in the participation level. Originality/value: These results affirmed the importance of psychological factors when exploring new technological platforms, as the paper proposes that individuals may behave differently in various technological environments due to their psychological characteristics. The study expanded current research about a popular communication tool, WhatsApp, by examining it within the special context of WhatsApp groups. This focus enables researchers to follow the special dynamics that take place in a new technological platform.